Implementasi Model Penilaian Unjuk Kerja Dalam Pembelajaran Matematika Berbasis Lesson Study Di SMP Muhammadiyah 1 Kartasura - Setyaningrum, Wulan Agus; , Dr. Sumardi, M.Si (2016)
ABSTRACT The purpose of this study was to describe the understanding of teachers in SMP Muhammadiyah 1 Kartasura on performance assessment, describing the implementation of performance assessment in mathematics-based lesson study, and describe the obstacles in mathematics-based lesson study with performance assessment. Forms of this research is descriptive qualitative. The data source consists of a process of learning and assessment. Data collection techniques in the study were (1) interview (2) field notes and (3) documentation. To test the validity of the data using triangulation sources and triangulation techniques. Data analysis techniques used in the study are (1) data collection (2) data reduction (3) presentation of data (4) conclusion. It can be concluded that: (1) teachers do not understand about performance assessment, it is because teachers have not been able to draw up an assessment rubric of performance (2) performance can familiarize students demonstrate its performance to understand and solve the problem, the increasing improvement of interaction of students with students, teachers and students, and improving the performance, quality of teachers. An increase in student learning outcomes 78.9 the first meeting, a second meeting 74, the third meeting of 80.94, and the fourth meeting of 91.25 (3) Constraints in the implementation of such learning, creation of student worksheets, split time in carrying out the study, manufacture scoring rubric work method. Keywords: implementation, lesson study, learning, performance assessment